The Ignatian Matrix of Henri De Lubac's Thought on Temptation, Ascesis, and the Homo Ecclesiasticus. (19th December 2013) - Ruddy, Christopher
Abstract : This article argues that Henri de Lubac's conception of the homo ecclesiasticus has deep roots in the spirituality of Ignatius of Loyola. Drawing upon Splendor of the Church, the article first presents de Lubac's vision of the homo ecclesiasticus and his or her temptations; particularly important here is what de Lubac calls the 'camouflage of the good' and the consequent importance of discernment and asceticism. The article concludes by analyzing the Ignatian matrix of de Lubac's thought, especially its emphasis on the discernment of spirits, a generous catholicity, and the inseparability of the spiritual and the ecclesial.